CD40L induces inflammation and adipogenesis in adipose cells – a potential link between metabolic and cardiovascular disease - Missiou, Anna; Wolf, Dennis; Platzer, Isabel; Ernst, Sandra; Walter, Carina; Rudolf, Philipp; Zirlik, Katja; Köstlin, Natascha; Willecke, Florian K.; Münkel, Christian; Schönbeck, Uwe; Libby, Peter; Bode, Christoph; Varo, Nerea; Zirlik, Andreas (Thrombosis and Haemostasis, 2010)
CD40L figures prominently in atherogenesis. Recent data demonstrate elevated levels of sCD40L in the serum of patients with the metabolic syndrome (MS). This study investigated the role of CD40L in pro-inflammatory gene expression and cellular differentiation in adipose tissue to obtain insight into mechanisms linking the MS with atherosclerosis. Human adipocytes and preadipocytes expressed CD40 but not CD40L. Stimulation with recombinant CD40L or membranes over-expressing CD40L induced a time- and dose-dependent expression of IL-6, MCP-1, IL-8, and PAI-1. Supernatants of CD40L-stimulated adipose cells activated endothelial cells, suggesting a systemic functional relevance of our findings. Neutralising antibodies against CD40L attenuated these effects substantially. Signalling studies revealed the involvement of mitogen-activated protein kinases and NFκB. Furthermore, stimulation with CD40L resulted in enhanced activation of C/EBPα and PPARγ and promoted adipogenesis of preadipose cells in the presence and absence of standard adipogenic conditions. Finally, patients suffering from the metabolic syndrome with high levels of sCD40L also displayed high levels of IL-6, in line with the concept that CD40L may induce the expression of inflammatory cytokines in vivo in this population. Our data reveal potent metabolic functions of CD40L aside from its known pivotal pro-inflammatory role within plaques. Our data suggest that CD40L may mediate risk at the interface of metabolic and atherothrombotic disease.
Keywords: CD40L; adipocytes; preadipocytes; inflammation; metabolic syndrome